THE COLLAPSE OF THE INTELLIGENTSIA IDEOLOGY: THE CAUSES OF FAILURE (CULTURAL AND PHILOSOPHICAL CONTEXT OF THE LATE 19TH – EARLY 20TH CENTURIES IN RUSSIA, BASED ON THE BOOK ABOUT THE RUSSIAN INTELLIGENTSIA «VEHI») - S. V. Zarutskaya (Вестник Кемеровского государственного университета, 2014)
The paper examines the moral and ethical views of the Russian intelligentsiain the late 19th – early 20th  centuries: its vocation and role, and errors of outlook. The main result of the study is finding that the failure of the intelligentsia’s activities is primarily a failure of ideology, so this issue is not political issue, but cultural philosophical and ethical.